Innovation Principles- AF186- 202201 - Herrera Indacochea, Juan Gabriel (2022)
Innovation Principles and Environments Course Overview: This course will teach you specific methods to assess and understand the industry, customers, and competitors for a new venture. You will then learn how to translate those insights into a winning venture idea, a business model, and set of distinctive new products and services. With this venture strategy in hand, you will then learn how to best raise venture financing, how to write a powerful business plan, and create a compelling pitch for investors. This course will show how these methods can be applied for corporate ventures as well as startups. For those students who wish to start their own venture, today or at some point in the future, this is the ideal course to learn real-world new venture planning. It will also be valuable for students who work for a large corporation and want to create entirely new businesses within that corporation. Prerequisite Requirements: No prior knowledge is assumed in this course. As such, there are no prerequisite requirements for ENTR 420R (UPC: AF186).